"a journey must be driven by mission and passion not by confusion" - F. Seling, Tenning; Wee, Cindy; Akir, Oriah; Wan Hassan, Sharifah Zakiah; Ramakrishnan, Prabha; Pereira, Helen; Ghazali, Azlina (UiTM Sarawak, 2004)
The arena was set for the Sarawak campus to grapple over issues relating to quality initiatives inside campus. It was a two-day session at Merdeka Palace Hotel. Soon after the organizers drew the rules of battle, volleys of views were hurled around the room, each time a leader of the various quality committees presenting a synopsis of its activities. Shortcomings to planning were identified, failures in implementation were reflected upon, and successes and appreciations were recognised.